Factors influencing continuance intention of online shopping of generation Y and Z during the new normal in Vietnam - Binh Nguyen Thi; Thi Lan Anh Tran; Thi Thu Hien Tran; Thanh Thao Le; Phan Nhat Hang Tran; Minh Hieu Nguyen (Cogent Business & Management, 2022)
This study investigated the determinants of online shopping continuance intention of Generation Y and Z during the new normal. A conceptual framework, which was an extension of the Technology Acceptance Model, was empirically tested using partial least squares structural equation modelling, multi-group analysis technique, and the data collected from 847 Gen Y-ers and Gen Z-ers in Hanoi, Vietnam during March 2022. The results revealed that facilitators of repurchase intention included perceived usefulness, perceived ease of use, satisfaction, and environmental awareness while perceived risks of online shopping served as a barrier. Notably, the barrier was found to affect Gen Y's repurchase intention more severely. Personalization was not directly associated with the intention but had strong indirect effects through perceived usefulness, perceived ease of use, and satisfaction. The risk of COVID-19 was not a predictor of online repurchase intention. Understanding of the continuance intention of online shopping among consumers from different generations in an emerging country during the new normal may aid to enhance the quality of decision-making. Specifically, platforms and sellers should adopt customized marketing programs towards Gen Y and Gen Z. Additionally, a user-friendly and informative purchasing process with personalized features should be formulated. Demonstrating online shopping as a green behavior would be useful. This study differs from earlier research by considering and comparing factors influencing the intention to keep shopping online of Gen Y and Gen Z in a developing country when the COVID-19 is well controlled.
Keywords: 650; COVID-19; Generation; Hanoi; Online shopping; Personalization; PLS-SEM; TAM